Liberal Economics : New Zealand Free Trade Agreements - Ridings, Penelope (Ekonomie liberalne : nowozelandzkie porozumienie o wolnym handlu, 2010)
Riding the crest of the "third wave" of regionalism, New Zealand has entered into free trade agreements with an increasing number of bilateral and regional partners. The focus has been on the Asia-Pacific, consistent with its economic and trade potential. The paper argues that if New Zealand is to prosper, particularly as an agricultural country, it must continue to pursue a trade liberalisation agenda. Political and strategic considerations, in addition to economic rationale, play an important role to this end and have largely driven New Zealand's integration into the Asia-Pacific. This integration can provide a catalyst for developing political and economic relations with other outside the Asia-Pacific. This potential may be more significant than the international political importance or size of New Zealand's economy would suggest.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 134, s. 115-130
Keywords: free trade agreements; liberal economics; New Zealand